(untitled) (Conversatoria Linguistica, 2019)
The aim of the paper is to describe and analyse the contemporary event Na Iwana, na Kupała in the context of field research material concerning traditional summer solstice rites. The author analyses both publications of ethnographic material from the region of Bielsk Podlaski and interviews with local people made by himself. In the Podlasie district an East Slavonic (Ukrainian) variant of the summer solstice ritual existed, which, in spite of similarities on the general level (location near water, throwing garlands of flowers into the water, use of fire), differs in details from the typical Polish Midsummer Night. The present-day event discussed in the paper draws only slightly on the authentic folk culture, referring to the Ukrainian variation of the summer solstice ritual. In practice, it functions as a contemporary mass event, close to the popular culture idiom. Apart from the aesthetic, ludic and playful function, the event called Na Iwana, na Kupała has also an important role of integrating the local Ukrainian minority.